The Exosporium of Bacillus megaterium QM B1551 Is Permeable to the Red Fluorescence Protein of the Coral Discosoma sp. - Lanzilli, Mariamichela; Donadio, Giuliana; Addevico, Roberta; Saggese, Anella; Cangiano, Giuseppina; Baccigalupi, Loredana; Christie, Graham; Ricca, Ezio; Isticato, Rachele (Frontiers in Microbiology, 2016)
Bacterial spores spontaneously interact and tightly bind heterologous proteins. A variety of antigens and enzymes have been efficiently displayed on spores of Bacillus subtilis, the model system for spore formers. Adsorption on B. subtilis spores has then been proposed as a non-recombinant approach for the development of mucosal vaccine/drug delivery vehicles, biocatalysts, bioremediation and diagnostic tools. We used spores of B. megaterium QM B1551 to evaluate their efficiency as an adsorption platform. Spores of B. megaterium are significantly larger than those of B. subtilis and of other Bacillus species and are surrounded by the exosporium, an outermost surface layer present only in some Bacillus species and lacking in B. subtilis. Strain QM B1551 of B. megaterium and a derivative strain totally lacking the exosporium were used to localize the adsorbed monomeric Red Fluorescent Protein (mRFP) of the coral Discosoma sp., used as a model heterologous protein. Our results indicate that spores of B. megaterium adsorb mRFP more efficiently than B. subtilis spores, that the exosporium is essential for mRFP adsorption, and that most of the adsorbed mRFP molecules are not exposed on the spore surface but rather localized in the space between the outer coat and the exosporium.